History's Ethical Demand: Memory, Denial, and Responsibility in the Wake of the Holocaust. Issue 2 (4th March 2019) - Frie, Roger
Abstract : What does it mean to discover an unspoken Nazi past in one's own family? In a moment defined by chance and circumstance, I discovered that my German grandfather had joined the Nazi Party. Using my family's struggle with memory as a site of inquiry, I examine the process of remembering, its transmission, and dissociation, particularly as it relates to past and present perpetrator groups. What lurks in the silences that are passed down between generations? How does our collective response to history's atrocities shape what we what we know and remember as individuals? How do we define the moral obligations of memory, or understand the power of dissociation more than seven decades after the Holocaust? When does complacency in the face of past or present injustice make us complicit? Any answer to these questions points to the complexity of memory and the ethical demands of history. Connections between collective crimes of the past and social injustices in the present are considered and different forms of historical awareness and personal responsibility are discussed. In the face of overt prejudice and racism, "history's call" and the work of psychoanalysis are inherently related.